The development of a policy brief on physical activity and health in Africa for children and adolescents with disabilities: COVID-19 and beyond - Rowena Naidoo; Verusia Chetty; Marie E.M. Young; Phindile E. Mahlalela; Philippe J. Gradidge; Soraya Maart; Dané Coetzee; Brett Smith; Estelle Lambert (African Journal of Disability, 2022)
No abstract availbale.